The musculoskeletal system of humans is not tuned to maximize the economy of locomotion - Carrier, D. R.; Anders, C.; Schilling, N. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Humans are known to have energetically optimal walking and running speeds at which the cost to travel a given distance is minimized. We hypothesized that "optimal" walking and running speeds would also exist at the level of individual locomotor muscles. Additionally, because humans are 60-70% more economical when they walk than when they run, we predicted that the different muscles would exhibit a greater degree of tuning to the energetically optimal speed during walking than during running. To test these hypotheses, we used electromyography to measure the activity of 13 muscles of the back and legs over a range of walking and running speeds in human subjects and calculated the cumulative activity required from each muscle to traverse a kilometer. We found that activity of each of these muscles was minimized at specific walking and running speeds but the different muscles were not tuned to a particular speed in either gait. Although humans are clearly highly specialized for terrestrial locomotion compared with other great apes, the results of this study indicate that our locomotor muscles are not tuned to specific walking or running speeds and, therefore, do not maximize the economy of locomotion. This pattern may have evolved in response to selection to broaden the range of sustainable running speeds, to improve performance in motor behaviors not related to endurance locomotion, or in response to selection for both.